2012
DOI: 10.1051/epjconf/20122501037
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the effect of liquid viscosity on slug flow in small diameter bubble column

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The liquid properties, such as liquid viscosity and surface tension, play important roles in the hydrodynamics and bubble coalescence and breakup. Intensive work has been done to study the effect of liquid viscosity, showing that increasing liquid viscosity significantly inhibits bubble breakup at higher liquid viscosities and enhances bubble coalescence in the range of low viscosity . Therefore, increasing liquid viscosity leads to the formation of larger bubbles and decreases total gas holdup in the bubble column .…”
Section: Introductionmentioning
confidence: 99%
“…The liquid properties, such as liquid viscosity and surface tension, play important roles in the hydrodynamics and bubble coalescence and breakup. Intensive work has been done to study the effect of liquid viscosity, showing that increasing liquid viscosity significantly inhibits bubble breakup at higher liquid viscosities and enhances bubble coalescence in the range of low viscosity . Therefore, increasing liquid viscosity leads to the formation of larger bubbles and decreases total gas holdup in the bubble column .…”
Section: Introductionmentioning
confidence: 99%
“…where Fr is obtained from Eqs. (27) to (32). On the average, a good agreement exists between the structure velocity from the ECT and that measured from the high-speed camera.…”
Section: Structure Velocity Comparisonmentioning
confidence: 60%
“…In a recent Quan (2011) pointed out that an increase in the liquid viscosity increases the viscous drag on the rising bubble, thereby tending to elongate the bubble. In a similar experimental work, study, Kajero et al (2012) indicated that the relative elongation of the bubble with increase in liquid viscosity may be characteristic to flow inside tubes, and that the relative elongation with increase in viscosity will be pronounced for smaller tube diameters. A comparison of the lengths of the Taylor bubbles (l b ) obtained from using Newtonian and non-Newtonian treatment of the liquid viscosity is shown in Fig.…”
Section: Validationmentioning
confidence: 89%
“…Kang et al (2010) carried out similar computational simulations using a front-tracking Volume-Of-Fluid (VOF) technique and concluded that the Eotvos number (Eo) and Archimedes number (Ar) significantly influenced the shape of the bubble; greater Eo and Ar resulted in longer bubble tail and a larger wake behind the bubble. In a recent experimental study on slug flows, Kajero et al (2012) characterised the effects of viscosity over the range 5-5000 m Pa-s on the length of Taylor bubbles, liquid film thickness, pressure gradients, and slug intermittencies, for superficial gas velocities in the range 0.02-0.361 m/s. They pointed out that the length of Taylor bubbles, the liquid film thickness adjacent to the bubble, and the pressure gradient in the slug, increase whereas the slug frequency and length of liquid slug decrease with an increase in liquid viscosity.…”
Section: Introductionmentioning
confidence: 99%